IMPLEMENTASI STRATEGI MARKETING MIX DALAM UPAYA MENINGKATKAN JUMLAH PESERTA DIDIK DI TK AL HUDA KOTA MALANG - Azizah Nurul Fadlilah; Saidah Masfiah (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2021)
This research aims to explain the implementation of marketing mix strategy in an effort to increase the number of students in Al Huda Kindergarten malang. This type of research belongs to qualitative research. Data is collected using observation, interview, and documentation techniques. The data analysis step consists of data presentation, data reduction, and then drawing conclusions. The results showed that Al Huda Kindergarten successfully used a marketing mix strategy in an effort to increase the number of students. In this effort, the marketing mix strategy used in the form of 7P method, which consists of: product, price, place, promotion, people, physical evidence, and process. The products offered by Al Huda Kindergarten are Islamic religious-based schools and care about the environment with a superior program of junk blessings. The cost stipulated adjusts the economic level of the surrounding residents. The location of the school is strategic. Promotional activities are conducted with print media, online, and into the field. Quality human resources and continuous efforts to develop. The physical evidence of Al Huda Kindergarten has good infrastructure and is constantly updated. While the learning process is carried out using a group learning model based on the angles of the activity.